1984
DOI: 10.1007/bf00427688
|View full text |Cite
|
Sign up to set email alerts
|

The effects of chronic lithium on behavioral and biochemical indices of dopamine receptor supersensitivity in the rat

Abstract: The effects of dietary lithium on several indices of dopamine receptor supersensitivity were examined in rats during withdrawal from chronic administration of haloperidol. Chronic haloperidol enhanced the locomotor stimulant action of d-amphetamine, and this effect was attenuated by lithium. In contrast, lithium did not affect the amphetamine response in animals that had not previously received haloperidol. Apomorphine-induced hypothermia was not influenced by the chronic haloperidol treatment. On the other ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…LiCl-fed rats gained weight more slowly than did control rats, as has been reported (Pittman et al, 1984). At the time of surgery, the LiCl-fed rats weighed about 20% less than the control diet-fed group (254721 g, n ¼ 26 vs 308711 g, n ¼ 24, po0.0001).…”
Section: Physiological Parameters and Behavioral Responsessupporting
confidence: 70%
See 1 more Smart Citation
“…LiCl-fed rats gained weight more slowly than did control rats, as has been reported (Pittman et al, 1984). At the time of surgery, the LiCl-fed rats weighed about 20% less than the control diet-fed group (254721 g, n ¼ 26 vs 308711 g, n ¼ 24, po0.0001).…”
Section: Physiological Parameters and Behavioral Responsessupporting
confidence: 70%
“…However, lithium's effects on dopaminergic neurotransmission are not agreed upon, as lithium is reported to inhibit (Engel and Berggren, 1980;Friedman and Gershon, 1973), increase (Fadda et al, 1980;Hesketh et al, 1978), or have no effect (Bliss and Ailion, 1970;Ho et al, 1970) on brain dopamine turnover. Data on lithium's effects on brain dopaminergic D 2 -like receptor density also are conflicting (DziedzickaWasylewska and Wedzony, 1996;Reches et al, 1982;Staunton et al, 1982b;Wajda et al, 1983), as are data on its ability to modify haloperidol-induced supersensitivity (Carvey et al, 1990;Gallager et al, 1978;Pert et al, 1978;Pittman et al, 1984;Reches et al, 1982;Staunton et al, 1982a).…”
Section: Introductionmentioning
confidence: 99%
“…Original findings that chronic lithium administration interfered with the development of DA postsynaptic supersensitivity (Pert et al, 1978) could not be confirmed by subsequent studies (Bloom et al, 1983;Pittman et al, 1984;Reches et al, 1984;Staunton et al, 1982). In the report by Carli et al (1994) (Carli et al, 1994), which revealed biphasic curves, and increased inhibition constants of the high-affinity sites in the neostriatum after chronic lithium administration.…”
Section: Introductionmentioning
confidence: 73%
“…The significance of these observations is not clear. In many animal studies it is reported that lithium given by acute or divided treatments may prevent the changes in dopamine receptor sensitivity following dopamine antagonist treatments (Klawans et al 1977;Pert et al 1978;Gallagher et al 1978;Verimer et al 1980), but in other studies where dietary lithium preparations have been used, when administration may be considered to be more persistent, the reports have shown little or no effect of lithium to modify the behavioural and biochemical changes caused by the neuroleptic drugs (see Pittman et al 1984). Is it possible that the routes of lithium administrations to achieve persistent or fluctuating levels of lithium may contribute to the discrepancies observed in the above experiments?…”
Section: Discussionmentioning
confidence: 99%
“…Whilst in some animal models lithium has been found to antagonise hyperactivity or increased responding caused by drugs or electrical stimulation, such changes are non-cyclical and the role of dopamine is not clear, or is obscured by an involvement of noradrenaline (see review by Samuel and Gottesfeld 1973). Furthermore, animal studies investigating the possibility that lithium may exert its therapeutic effect by preventing the development of supersensitive dopamine receptors have produced conflicting data (see -Pittman et al 1984).…”
mentioning
confidence: 99%